Sweet/dessert foods are more appealing to adolescents after sleep restriction. - Stacey L Simon; Julie Field; Lauren E Miller; Mark DiFrancesco; Dean W Beebe (PLoS ONE)
Study objective Examine the effect of experimental sleep restriction (SR) on adolescents' subjective hunger and perceived appeal of sweet/dessert foods versus other foods. A secondary goal was to replicate previous findings on the effects of SR on dietary intake. Design Randomized cross-over sleep restriction-extension paradigm. Setting Sleep was obtained and monitored at home. Outcome measures were gathered during office visits. Participants 31 typically-developing adolescents aged 14-17 years. Interventions The three-week protocol consisted of a baseline week, followed randomly by five consecutive nights of SR (6.5 hours in bed) versus healthy sleep duration (HS; 10 hours in bed), a 2-night wash-out period, and a 5-night cross-over. Measurements Sleep was monitored via actigraphy. The morning after each experimental condition, teens rated their hunger, underwent a 24-hour diet recall interview, and rated the appeal of a series of pictures of sweet/dessert foods (e.g., ice cream, candy) and non-sweets (meat, eggs, fruits, vegetables). Results Teens rated pictures of sweet/dessert foods to be more appealing after SR than after HS (Cohen's d = .41, t = 2.07, p = .045). The sleep manipulation did not affect self-reported hunger or the appeal of non-sweet foods (p >.10). Consistent with our prior work, intake of overall calories was 11% higher and consumption of sweet/dessert servings was 52% greater during SR than HS. Conclusions Adolescent SR appears to increase the subjective appeal of sweet/dessert foods, indicating a potential mechanism by which SR might contribute to weight gain and the risk for obesity and chronic illness.